Agriculture technology business in Malaysia: knowledge sharing from other agro-technology economy-based countries - Mastoi, Qurat-ul-ain; Abdullah, Istikoma; Ahmad Dahlan, Abdul Rahman (2015)
This paper demonstrates factory farm-technology in Malaysia and includes a literature brush-up from a few other countries. This study compares the Agro technology transformation program in several countries; Taiwan, South Korea, Thailand, Israel and Malaysia. How are they improving their economy, though agribusiness? The concept of advanced technologies in agronomic systems has been given a significant role in the melioration of agricultural creations e.g. sustainable agriculture, livestock production and Craw yield, in order to maintain food security. This paper illustrates what form of sweetening needs to heighten the Malaysia economy through agronomy, communion and knowledge of agricultural technology and exploring the reasons why the agriculture economy is back on the policy docket of Malaysia.